Imidazolidinyl urea activates mast cells via MRGPRX2 to induce non-histaminergic allergy. Issue 3 (29th April 2021) - Gao, Jiapan; Che, Delu; Du, Xueshan; Zheng, Yi; Jing, Huiling; Wang, Nan
Abstract: Imidazolidinyl urea (IU) is used as an antimicrobial preservative in cosmetic and pharmaceutical products. IU induces allergic contact dermatitis, however, the mechanism has not yet been elucidated. Mas-related G protein-coupled receptor-X2 (MRGPRX2) triggers drug-induced pseudo-allergic reactions. The aims of this study were to determine whether IU activated mast cells through MRGPRX2 to further trigger contact dermatitis. Wild-type (WT) and Kit W-sh /HNihrJaeBsmJNju (MUT) mice were treated with IU to observe its effects on local inflammation and mast cells degranulation in vivo . Laboratory of allergic disease 2 cells were used to detect calcium mobilization and release of inflammatory mediators in vitro . WT mice showed a severe local inflammatory response and contact dermatitis, whereas only slight inflammatory infiltration was observed in MUT mice. Thus, MRGPRX2 mediated the IU-induced activation of mast cells. However, histamine, a typical allergen, was not involved in this process. Tryptase expressed by mast cells was the major non-histaminergic inflammatory mediator of contact dermatitis. IU induced anaphylactic reaction via MRGPRX2 and further triggering non-histaminergic contact dermatitis, which explained why antihistamines are clinically ineffective against some chronic dermatitis.